ANALISIS FAKTOR YANG MEMPENGARUHI MINAT PESERTA DIDIK DALAM MELAKUKAN AKTIVITAS KEBUGARAN JASMANI DI SMP MUHAMMADIYAH 4 SAMBI BOYOLALI - Setia Budi, Taufik; Nur Subekti; Nurhidayat Nurhidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to determine student’s interest in participating in physical fitness activities at SMP Muhammadiyah 4 Sambi Boyolali. This study is a quantitative descriptive study using a survey method, with data collection techniques employing a questionnaire as the instrument and measuring using a Likert scale. Based on the data results and the conclusions of this study. It was found that among students interests in participating in physical fitness activities at SMP Muhammadiyah 4 Sambi Boyolali, the extrinsic factor of facilities and infrastructure received the highest score, with 50% strongly agreeing; followed by the intrinsic factor of maintaining health, with 47% strongly agreeing; and the intrinsic factor of personal motivation, with 40% strongly agreeing.